A novel model of kinetics and thermodynamics for shale gas adsorption-diffusion - Liu, Jianyi; Yuan, Hua; Gu, Congyue; Liu, Zhibin; Jiang, Lu; Wen, Yimin; Yan, Xiaojie; Ding, Qunchao (Petroleum science and technology, 2025)
The study of adsorption-diffusion kinetics in shale gas reservoirs is crucial for predicting reserves and assessing production. Although some scholars have proposed adsorption-diffusion kinetics models, there are few models and interpretation methods that systematically consider Arrhenius's thermodynamics parameters and actual adsorption gas concentration. In this study, we propose a novel model for analyzing the kinetics processes of adsorbed gas and free gas in shale. The analysis of adsorbed gas kinetics experimental data indicates a negative correlation between temperature and the adsorption-diffusion equilibrium time. Sensitivity analysis of the parameters reveals that three parameters (the diffusion activation energy, adsorption activation energy, and desorption pre-exponential factor) are positively correlated with adsorption-diffusion equilibrium time, whereas the other three parameters (the diffusion pre-exponential factor, adsorption pre-exponential factor, and desorption activation energy) are negatively correlated. Furthermore, we find that higher temperatures lead to lower concentrations of free gas at equilibrium state. Larger radius positions in spherical particles tend to reach adsorption-diffusion equilibrium earlier. Compared to the traditional diffusion kinetics model, the proposed novel model exhibits a significant lag effect in the calculated equilibrium time and more accurately describes the gas adsorption-diffusion kinetics equilibrium process.